Social relationships in IT project teams: its role, complexity and the management thereof - Leonard, Awie; Zyl, Dawie van (International Journal of Information Systems and Project Management, 2022)
Compared to other projects, information technology (IT) projects, characterized by emergency and uncertainty, are unique. To implement an IT project successfully, many aspects need to be monitored and carefully controlled and managed. One such aspect is social relationships. All IT professionals are exposed to, and in many cases involved, in the phenomenon of social relationships. These relationships are used by software project team members for personal as well as professional purposes. In most cases the impact of these relationships on the success or failure of any given IT project is ignored by IT management. Little attention is given thereto in the literature and this paper attempts to make a contribution in terms of giving a broad perspective of the complexity, the impact, as well as the management of such relationships. This paper demonstrates that these relationships play a significant role and should be managed in such a way that the team members and the project as a whole can reap the benefits thereof. A conceptual framework is proposed for the management of these relationships.